An Alkyne Diboration/6π‐Electrocyclization Strategy for the Synthesis of Pyridine Boronic Acid Derivatives. (5th April 2016) - Mora‐Radó, Helena; Bialy, Laurent; Czechtizky, Werngard; Méndez, María; Harrity, Joseph P. A.
Abstract: A new and efficient synthesis of pyridine‐based heteroaromatic boronic acid derivatives is reported through a novel diboration/6π‐electrocyclization strategy. This method delivers a range of functionalized heterocycles from readily available starting materials.